2017
DOI: 10.1016/j.snb.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole linear actuation tuned by phosphotungstic acid

Abstract: Co-doping polypyrrole (PPy) with dodecylbenzenesulfonate and multicharged phosphotungstate anions (PT) from the phosphotungstic acid (PTA) led to free-standing PPy/DBS-PT films, which were studied for their linear actuation properties. FTIR and Raman spectra revealed that PT was successfully embedded in PPy/DBS during electropolymerisation. Isometric stress and isotonic strain measurements in aqueous electrolyte under various electrochemical experiments showed an increase in the obtainable strain and stress, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The results of the specific capacitance of the films showed that despite the different solvents, the values were close-in the range of 75 ± 2.4 F g −1 at 0.0025 Hz and, as expected, decreasing with increasing frequency [56]. Conducting polymers are defined as pseudo-capacitors due to their redox reactive nature [57], while strongly dependent on film thickness, specific capacity values of 100 F g −1 have been reached with PPy in LiTFSI-aq electrolyte under similar conditions [58]. As the PIL part of the material is not participating in the redox charging and with thicker films, the specific capacitance cannot reach as high, but on the other hand, the positively charged polycations inside the PPyPIL make the electrochemical behavior much more stable and also independent of the solvent.…”
Section: Discussionsupporting
confidence: 67%
“…The results of the specific capacitance of the films showed that despite the different solvents, the values were close-in the range of 75 ± 2.4 F g −1 at 0.0025 Hz and, as expected, decreasing with increasing frequency [56]. Conducting polymers are defined as pseudo-capacitors due to their redox reactive nature [57], while strongly dependent on film thickness, specific capacity values of 100 F g −1 have been reached with PPy in LiTFSI-aq electrolyte under similar conditions [58]. As the PIL part of the material is not participating in the redox charging and with thicker films, the specific capacitance cannot reach as high, but on the other hand, the positively charged polycations inside the PPyPIL make the electrochemical behavior much more stable and also independent of the solvent.…”
Section: Discussionsupporting
confidence: 67%
“…PPy doped with DBS − is one of the best studied types of conducting polymer materials, found in various formations in micro-fabrication [ 1 ] such as micro-robotic devices [ 2 , 3 ] biomedical applications [ 4 ], biochips to trigger cell growth over actuation [ 5 ] and, recently, smart textile fabrications [ 6 ]. Addition of charged molecules such as polyoxometalates (Keggin type [ 7 ], phosphotungstic acid (PTA, PW 12 O 40 3− )) forming PPyDBS-PT composites revealed strain in aqueous electrolyte in range of 5.2% [ 8 ]. Additional incorporation of meso-porous carbide-derived carbon (CDC) particles forming PPyDBS-PT-CDC (PPyCDC) linear films [ 9 ] had strain in the range of 12% while PPyDBS linear actuators strain values varied at 4–6% strain depending on the choice of electrolyte applied [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for polypyrrole, Hara et al [68] reached the stress of 20.4 MPa with TBACF 3 SO 3 and the strain of 26% with bis(trifluoromethanesulfonyl)imide (TFSI) anion. New conducting polymers have been recently fabricated with different dopants, such as PPy doped with dodecylbenzenesulphonate (DBS) (PPy/DBS) [69], and further with phosphotungstate anions (PT) to give PPy/DBS-PT [70] and with carbide-derived carbon (CDC) to give PPy/DBS-CDC-PT [71] linear actuators. These conducting polymers have been applied in wearable devices [72] and even in tissue engineering [73], which are shown in Fig.…”
Section: Soft Linear Actuators Driven By Ionic Diffusionmentioning
confidence: 99%